(untitled) (Psychology Travelogs, 2021)
The article presents an analysis of psychological and pedagogical research on gender roles in adult interaction. The content of the concept of gender as a culturally determined and socially constructed category, which characterizes certain expectations about the roles and behavior of men and women, as well as the relationship between them. The concept of gender interaction is considered as a set of social-role relationships, reflected in various forms of relationship between people as members of a certain sex and gender, which arise and are formed in the process of their joint life in all its spheres. The notion of gender role as a function of personality, which provides reproduction of gender stereotype, is revealed; a pattern of behaviors and relationships that allow other people to draw conclusions about an individual’s male or female gender. Gender roles have extremely important consequences in the lives of men and women, as they affect the interaction and relationships of individuals with other people, give men and women certain places in the social structure in which both sexes identify themselves, formulate their own goals and values. The peculiarity of gender roles is that we do not choose them, they belong to the type of assigned roles. The status of the future husband or future woman is obtained by the child at birth, and then in the process of gender socialization the child learns to perform a particular gender role. The norms of women’s and men’s gender roles are analyzed and the course of changes in the modern society of views on this issue is revealed. These changes are related to the idea that traditional gender roles constrain personal development and realization of the existing potential of the individual, complicate the interaction between representatives of different gender groups and within them.